De “sostén” a “decidido apoyo” : población y contrainsurgencia en las revistas militares. El Salvador (1961-1972) - Lucrecia Molinari (Nuevo mundo - Mundos Nuevos, 2017)
This paper aims to analyze and periodize the characterization of the population held in the context of counterinsurgency, doctrine that guided the actions of the armed forces, security forces and paramilitary organizations in El Salvador between 1961 and 1972.